Heard on the Iowa Birdline, April 1-June 10, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Summary of the Iowa Birdline update for April 1-June 1, 1994. Highlights of the update include April sightings of a Western Tanager, a Spragues's Pipit, and a potential first state record observation of a Fish Crow. Other interesting reports include sightings of a Purple Gallinule, a Ruff, a large assortment of unusual waterfowl at Silver Lake in Worth County, and many rare bird sightings at Blue Lake in Monona County. Epson - sheet feed